As bases genéticas da personalidade, dos valores humanos e da preocupação com a honra - Araújo, Rafaella de Carvalho Rodrigues (2013)
When we estimate the influence effects of genetic and environmental factors on human beings, we aim to comprehend the extent to which the difference of each person, regarding their behaviors, may be assigned to each one of these factors, isolated and combined. Scholars not only of social psychology are already aware of how genetics might influence human behavior, which can be verified through literature, where it is already attributed to the biological bases a significant percentage of the causes and behavioral predispositions. Thus, from an ex post facto research, this paper has the main objective of verify the genetic basis of honor concern, human values and personality, and the influence of genetic inheritance on each of these constructs. It is believed that honor, for having stronger cultural aspects, will receive less influence from genetics, and personality, that presents the greatest influence from genetics, as it is inherently more constituted by biological factors than the social ones. Human values, then, would be located at an intermediate. Thus, this dissertation is based on the Functionalist Theory of Human Values, through the Basic Value Survey, as well as the Culture of Honour Scale and the Big Five Inventory to measure honor and personality, respectively, and a sociodemographic questionnaire. For this study, the sample consisted in 115 pairs of twins, 77 monozygotic (67%) and 38 dizygotic (33%), a total sample of 230 people. Among monozygotic, most were female (78%) with a mean age of 24.4 (SD = 6.85). In dizygotic, most also said to be female (71.1%) with a mean age of 21.9 (SD = 4.31). The results were divided into three sections. In the first one, means and correlations between pairs of twins were tested, in what concerns to each one of the factors of the three scales. It was observed that except for the correlations of social honor (r = .26, p < .05), female honor (r = .51, p < .001) and the normative subfunction (r = .52, p < .001), in both means and correlations between type of twin and construct, the monozygotic presented behaviors more similar than dizygotic twins. Then, estimates of heritability of behavior were calculated, noting that honor (M = .24, SD = .44) presented the lowest average, being followed by human values (M = .56, SD = .23) and personality (M = .63, SD = .19). Finally, using structural equation modeling, the fit indices (chi-square, AIC and RMSEA) for the models of genetic inheritance were tested. The results confirmed the model for all types of honor, for the subfunctions of excitement, existence and interactive and personality traits of neuroticism, openness to change and agreeableness. Furthermore, the hierarchy of importance of genetic inheritance among the three studied constructs was partially confirmed [honor (M = .18, SD = .19), values (M = .39, SD = .08) and personality (M = .39, SD = .62)]. Thus, it could be verified that all constructs have some genetic influence. Finally, as expected, the hierarchy of biological bases between them was confirmed, besides being evidenced the greatest similarity among monozygotic twins, as the results for this group were significantly higher than those presented by dizygotic twins, pointing to an effective genetic basis of human behavior.